2018
DOI: 10.21767/2049-5471.1000174
|View full text |Cite
|
Sign up to set email alerts
|

Stress Management Classes for Uninsured Free Clinic Patients in the United States

Abstract: Objective: Stress has become a growing public health concern in the United States (US). Uninsured, low-income or minority patients utilizing a free clinic are exposed to stress disproportionately across various areas of life. Health promotion programs regarding stress management have the potential to benefit vulnerable, low-income populations by reducing stress-related health issues. The purpose of this study was to describe and evaluate the "Stress-Management" education class taught at a free clinic that prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The clinic serves a diverse population, with patients originally from more than 50 countries. More than half of the patients speak Spanish and many of them have limited English proficiency [15]. The clinic relies on volunteer interpreters or patients' families and friends who are bilingual to help with patient care.…”
Section: Settingsmentioning
confidence: 99%
“…The clinic serves a diverse population, with patients originally from more than 50 countries. More than half of the patients speak Spanish and many of them have limited English proficiency [15]. The clinic relies on volunteer interpreters or patients' families and friends who are bilingual to help with patient care.…”
Section: Settingsmentioning
confidence: 99%
“…3 Socioeconomic status has been linked to health outcomes and substantial disparities across lifespans, which could be related to adverse stress levels. 4,5 A significant number of studies have identified that a lower socioeconomic status, including low levels of income and education, is associated with greater distress, resulting in high rates of morbidity and mental disorders among this population compared with those enjoying higher socioeconomic positions. 5,6 People with lower income levels are exposed to immense stress in various aspects of their lives, including threats to their quality of life and to safety.…”
mentioning
confidence: 99%